Reversal of neuromuscular block with sugammadex in five heart transplant pediatric recipients - Carlos,Ricardo Vieira (2018)
Abstract Heart transplantation is a frequent procedure in the treatment of end-stage cardiac dysfunction. Therefore, these patient populations will also be more frequent exposed to other more common surgical procedures after their transplantation. Anesthesiologist should be aware in their assessment of these patients, especially regarding some specific issues related to patients with a history of heart transplantation, like reversal of neuromuscular block. Several reports described that cholinesterase inhibitors drugs, like neostigmine, may produce a dose-dependent life-threatening bradycardia in heart transplant recipients while other publication described the safe use of neostigmine. Reversal of neuromuscular block with sugammadex is another possibility, but limited data exists in literature. We describe five cases in which successful reversal of neuromuscular block was performed with sugammadex in heart transplant pediatric recipients without sequale and discuss the reversal of neuromuscular block in this patient population.